STUDI KETERLAKSANAAN PEMBELAJARAN FISIKA BERBASIS SCIENTIFIC APPROACH DI SMA NEGERI KOTA YOGYAKARTA - Melkianus Suluh; Jumadi Jumadi (SekolahTinggi Keguruan dan Ilmu Pendidikan (STKIP), 2017)
This study aims to determine: (1) the implementations of physics learning based on scientific approach, (2) the relationship between teacher’s educational background with implementations scientific approach. This study was a survey research using a descriptive correlational approach. The research sample included 18 physics teachers spread in 10 state senior high schools in Yogyakarta city established with purposive sampling technique. The data were collected by using teachers questionnaires, observation sheets, and documentation sheet. The data were analized by using descriptive analysis and Spearman correlation analysis. Results of the study. (1) Implementations scientific approach in Yogyakarta State Senior High Schools has been running well. (2) There was positive and significant relationship between teachers educational background and Implementations Scientific Approach.